A polymer emulsion, a polymer composite diaphragm and its application in lithium battery diaphragm
By applying polymer emulsion and polyolefin coating on the lithium battery separator, the problems of heat shrinkage and lithium dendrites puncture during heating are solved, and a safer lithium battery separator design is achieved, reducing explosive combustion risk.
Patent Information
- Application Number
- CN202410634612.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-21
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2044-05-21
AI Technical Summary
The existing lithium battery separators shrink greatly when the heat rises, and cannot be closed in time, resulting in safety risks. The puncture of lithium dendrites through the separator may lead to short circuits of the positive and negative electrodes, increasing the risk of explosion and combustion.
The polymer emulsion is applied to the base film to reduce the closed-cell temperature of the membrane, provide an effective closed-cell effect, prevent the temperature from rising by melting the polymer, and produce inclusive protection of lithium dendrites through the polyolefin coating.
Significantly reduce the chance of explosion and combustion of lithium batteries, improve safety performance, ensure that the battery does not short circuit at abnormal temperatures, and enhance the protective effect of the diaphragm.
Smart Images

Figure BDA0004852160900000101 
Figure BDA0004852160900000111 
Figure BDA0004852160900000112
Abstract
Description
Technical Field
[0001] The invention belongs to the field of lithium battery separators, and in particular relates to a polymer emulsion, a polymer composite separator and applications thereof in lithium battery separators. Background Art
[0002] With the development of the new energy industry, the importance of lithium batteries has gradually emerged. As an energy source for energy storage, power and consumer products, lithium batteries have the advantages of high energy density, long cycle life and large capacity. Lithium batteries are mainly composed of positive and negative electrode materials, electrolytes and diaphragms. As one of the important parts, the diaphragm separates the positive and negative electrodes of the battery to prevent the two electrodes from contacting and short-circuiting. In addition, it also has the function of allowing electrolyte ions to pass through. The diaphragm is located between the positive and negative electrodes. Its main function is to separate the positive and negative active materials to prevent the two electrodes from short-circuiting due to contact. In addition, during the electrochemical reaction, it can maintain the necessary electrolyte and form a channel for ion movement.
[0003] When the battery is hit or the temperature rises abnormally, the diaphragm may shrink or break, causing a short circuit between the positive and negative electrodes, which may lead to explosion and combustion. When the lithium battery is in a charging state, lithium ions are deintercalated from the positive electrode material and flow to the negative electrode. When the charging voltage is higher than the rated maximum charging limit voltage, the number of lithium atoms remaining in the positive electrode material is greatly reduced, and the layered storage cells of the positive electrode material will collapse. If charging continues at this time, the lithium ions will fill the storage cells of the negative electrode material and accumulate in a dendritic crystal state on the surface of the negative electrode material to form lithium dendrites. These lithium dendrites may pierce the diaphragm and cause a short circuit between the positive and negative electrodes inside the battery. Similarly, when the charging current is too large, the lithium ions that do not have time to enter the storage cells will gather on the surface of the positive and negative electrode materials, and will also form lithium dendrites, which will bring great safety hazards.
[0004] It can be seen that the diaphragm plays a very important role in the safety performance of lithium batteries. Therefore, safety can be improved by improving the structural design of the diaphragm, or by disconnecting the battery in time in the early stage of temperature rise so that the current is no longer continuously generated, so as to protect the diaphragm and avoid serious shrinkage, thereby improving the protection of the battery. Most of the existing diaphragms are mainly PE, PP, polyester or PI films. PE and PP films shrink greatly during the heating process and cannot close the pores in time. Polyester and PI films cannot close the pores themselves, and cannot quickly and effectively produce a protection mechanism when risks occur. Summary of the invention
[0005] In view of the deficiencies of the prior art, the purpose of the present invention is to provide a high molecular polymer emulsion, which, when coated on a base film, can effectively reduce the closed-cell temperature of the diaphragm and provide an effective closed-cell effect, thereby reducing the probability of explosion and combustion of lithium batteries and improving the safety performance of lithium batteries.
[0006] The object of the present invention is to provide a polymer emulsion, wherein the melting point of the polymer emulsion is 115-130°C and the initial softening point is 70-90°C.
[0007] Preferably, the melting point of the polymer emulsion is 120-128°C and the initial softening point is 74-82°C.
[0008] Preferably, the D50 of the polymer emulsion is 0.3-6 μm.
[0009] More preferably, the D50 of the polymer emulsion is 2 to 3 μm.
[0010] Preferably, the polymer emulsion is spherical.
[0011] Preferably, the polymer emulsion comprises the following components by weight: 20-60 parts of polymer, 1.25-4.75 parts of emulsifier, and 62.5-116 parts of water. The polymer comprises polyolefin, and the weight average molecular weight of the polyolefin is 1000-10000 g / mol.
[0012] More preferably, the polymer emulsion comprises the following components by weight: 30-50 parts of polymer, 2-4 parts of emulsifier, and 80-100 parts of water, wherein the polymer comprises polyolefin, and the weight average molecular weight of the polyolefin is 2000-7000 g / mol.
[0013] More preferably, the weight average molecular weight of the polyolefin is 3000 to 5000 g / mol.
[0014] Preferably, the polyolefin includes at least one of polyethylene, polypropylene and Fischer-Tropsch wax.
[0015] More preferably, the polyolefin is selected from a combination of Fischer-Tropsch wax and polyethylene.
[0016] More preferably, the mass ratio of the Fischer-Tropsch wax to polyethylene is 6-10:1-5.
[0017] More preferably, the mass ratio of the Fischer-Tropsch wax to polyethylene is 5:1.
[0018] More preferably, the polyolefin is selected from a combination of Fischer-Tropsch wax and polypropylene.
[0019] More preferably, the mass ratio of the Fischer-Tropsch wax to polypropylene is 4-8:1-3.
[0020] More preferably, the mass ratio of the Fischer-Tropsch wax to polypropylene is 4:1.
[0021] Preferably, the emulsifier includes at least one of aliphatic alkylphenol polyoxyethylene ethers, benzylphenol polyoxyethylene ether, phenethylphenol polyoxyethylene ether, fatty alcohol polyoxyethylene ether and derivatives thereof, polyoxypropylene ether and derivatives thereof, fatty amine polyoxyethylene ether, fatty acid ethylene oxide adducts, castor oil ethylene oxide adducts and derivatives thereof, polyol fatty acid esters and ethylene oxide adducts thereof, diglycerol, fatty acid esters, diglycerol polypropylene glycol ether, glycerol polyoxyethylene ether, polyoxypropylene ether fatty acid esters, alkylphenol polyoxyethylene ether phosphates, phenethylphenol polyoxyethylene ether phosphates, fatty acid polyoxyethylene ester phosphates, alkylamine polyoxyethylene ether phosphates, and fatty alcohol polyoxyethylene ether phosphates.
[0022] Preferably, the polymer emulsion further comprises 4.5 to 10 parts of ceramic powder.
[0023] Preferably, the ceramic powder includes at least one of SiC ceramic powder, Al2O3 ceramic powder, ZrO2 ceramic powder, AlN ceramic powder, Si3N4 ceramic powder, B4C ceramic powder and BN ceramic powder.
[0024] Preferably, the ceramic powder is a combination of a first ceramic powder, a second ceramic powder and a third ceramic powder, the first ceramic powder has a particle size of 50 to 70 μm, the second ceramic powder has a particle size of 20 to 45 μm, and the third ceramic powder has a particle size of 0.5 to 2 μm.
[0025] More preferably, the first ceramic powder is selected from AlN ceramic powder, the second ceramic powder is selected from ZrO2 ceramic powder, and the third ceramic powder is selected from SiC ceramic powder.
[0026] Preferably, the weight ratio of the first ceramic powder, the second ceramic powder and the third ceramic powder is 1:1-3:0.5-2.
[0027] Another object of the present invention is to provide a polymer composite diaphragm, comprising a base film and a polyolefin coating composited on at least one side of the base film, wherein the material of the polyolefin coating comprises the polymer emulsion.
[0028] Preferably, the amount of the polymer emulsion is 80% to 90% of the material of the polyolefin coating in terms of mass percentage.
[0029] Preferably, the material of the polyolefin coating further comprises, by mass percentage, 2-3% of a dispersant and 8-17% of a binder.
[0030] Preferably, the base film includes at least one of a polyethylene base film and a polypropylene base film.
[0031] Preferably, the base film has a thickness of 3 to 20 μm.
[0032] Preferably, the polyolefin coating has a thickness of 1 to 6 μm.
[0033] Another object of the present invention is to provide a method for preparing a polymer composite diaphragm, comprising the following steps:
[0034] S1. Mixing the emulsifier and water, adding the polymer, heating and stirring to obtain a polymer emulsion;
[0035] S2. Mix the polymer emulsion, dispersant and adhesive, apply them evenly on the base film, and dry them to obtain a composite diaphragm.
[0036] Preferably, in S1, the heating temperature is 90-110° C., and the heating time is 0.5-1.5 hours.
[0037] Preferably, in S2, the dispersant includes at least one of polyurethane, polyethylene glycol, and polyvinyl alcohol.
[0038] Preferably, in S2, the adhesive includes at least one of carboxymethyl cellulose, hydroxyethyl cellulose, and polyurethane acrylate.
[0039] Preferably, in S2, the coating method includes at least one of rolling, spraying and brushing.
[0040] Another object of the present invention is to provide a method for preparing a polymer composite diaphragm, comprising the following steps:
[0041] S1. Mix the emulsifier and water, add the polymer and ceramic powder, heat and stir to obtain a polymer emulsion;
[0042] S2. Mix the polymer emulsion, dispersant and adhesive, apply them evenly on the base film, and dry them to obtain a composite diaphragm.
[0043] Preferably, in S1, the heating temperature is 90-110° C., and the heating time is 0.5-1.5 hours.
[0044] Preferably, in S2, the dispersant includes at least one of polyurethane, polyethylene glycol, and polyvinyl alcohol.
[0045] Preferably, in S2, the adhesive includes at least one of carboxymethyl cellulose, hydroxyethyl cellulose, and polyurethane acrylate.
[0046] Preferably, in S2, the coating method includes at least one of rolling, spraying and brushing.
[0047] Another object of the present invention is to provide application of the polymer composite membrane in lithium battery membranes.
[0048] Compared with the prior art, the present invention has the following beneficial effects:
[0049] (1) The polymer emulsion of the present invention is uniformly attached to the base film after coating. When the battery is working normally, it does not affect the performance of the battery itself. When the temperature rises abnormally, the polymer will melt first, thereby blocking the micropores on the base film, causing the battery to short-circuit, preventing the temperature from continuing to rise, and greatly reducing the probability of explosion and combustion of the battery.
[0050] (2) The present invention coats polymer emulsion on both sides of the base film. Due to the flexibility of the polymer itself, when lithium ions fill the storage cells of the negative electrode material, they will accumulate in a dendritic crystal state on the surface of the negative electrode material to form lithium dendrites. These lithium dendrites may pierce the diaphragm, causing a short circuit between the positive and negative electrodes inside the battery. The polyolefin coating can have good tolerance to puncture, thereby improving the protection of the diaphragm. DETAILED DESCRIPTION
[0051] In order to enable those skilled in the art to better understand the technical solutions in the present invention, the technical solutions in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.
[0052] Example 1: Preparation of polymer emulsion.
[0053] 1.25 g of benzylphenol polyoxyethylene ether and 116 g of water were mixed, 20 g of Fischer-Tropsch wax with a weight average molecular weight of 4000 g / mol was added, the mixture was heated to 100° C., and stirred for 1 hour to obtain a polymer emulsion.
[0054] Example 2: Preparation of polymer emulsion.
[0055] 4.75 g of diglycerol polypropylene glycol ether and 72.5 g of water were mixed, 60 g of polyethylene with a weight average molecular weight of 1000 g / mol was added, the mixture was heated to 100° C., and stirred for 1 hour to obtain a polymer emulsion.
[0056] Example 3: Preparation of polymer emulsion.
[0057] 2.75 g of glycerol polyoxyethylene ether and 94.5 g of water were mixed, 40 g of polypropylene with a weight average molecular weight of 10,000 g / mol was added, the mixture was heated to 100° C., and stirred for 1 hour to obtain a polymer emulsion.
[0058] Example 4: Preparation of polymer emulsion.
[0059] 2.75 g of glycerol polyoxyethylene ether and 94.5 g of water were mixed, 40 g of Fischer-Tropsch wax with a weight average molecular weight of 4000 g / mol was added, the mixture was heated to 100° C., and stirred for 1 hour to obtain a polymer emulsion.
[0060] Example 5: Preparation of polymer emulsion.
[0061] 2.75 g of glycerol polyoxyethylene ether and 94.5 g of water were mixed, 40 g of polyethylene with a weight average molecular weight of 1000 g / mol was added, the mixture was heated to 100° C., and stirred for 1 hour to obtain a polymer emulsion.
[0062] Example 6: Preparation of polymer emulsion.
[0063] 2.75 g of glycerol polyoxyethylene ether and 94.5 g of water were mixed, 33.3 g of Fischer-Tropsch wax with a weight average molecular weight of 4000 g / mol and 6.7 g of polyethylene with a weight average molecular weight of 1000 g / mol were added, heated to 100° C., and stirred for 1 hour to obtain a polymer emulsion.
[0064] Example 7: Preparation of polymer emulsion.
[0065] 2.75 g of glycerol polyoxyethylene ether and 94.5 g of water were mixed, 32 g of Fischer-Tropsch wax with a weight average molecular weight of 4000 g / mol and 8 g of polypropylene with a weight average molecular weight of 10000 g / mol were added, heated to 100° C., and stirred for 1 hour to obtain a polymer emulsion.
[0066] Example 8: Preparation of polymer emulsion.
[0067] Mix 1.25 g of benzylphenol polyoxyethylene ether and 111.5 g of water, add 20 g of Fischer-Tropsch wax with a weight average molecular weight of 4000 g / mol and 1 g of AlN ceramic powder with a particle size of 63 μm, 3 g of ZrO2 ceramic powder with a particle size of 28 μm, and 0.5 g of SiC ceramic powder with a particle size of 0.8 μm, heat to 100°C, stir for 1 hour, and obtain a polymer emulsion.
[0068] Example 9: Preparation of polymer emulsion.
[0069] Mix 4.75 g of diglycerol polypropylene glycol ether and 62.5 g of water, add 60 g of polyethylene with a weight average molecular weight of 1000 g / mol, 2.5 g of AlN ceramic powder with a particle size of 63 μm, 2.5 g of ZrO2 ceramic powder with a particle size of 28 μm, and 5 g of SiC ceramic powder with a particle size of 0.8 μm, heat to 100°C, stir for 1 hour, and obtain a polymer emulsion.
[0070] Example 10: Preparation of polymer emulsion.
[0071] Mix 2.75 g of glycerol polyoxyethylene ether and 86.5 g of water, add 40 g of polypropylene with a weight average molecular weight of 10,000 g / mol, 2 g of AlN ceramic powder with a particle size of 63 μm, 2 g of ZrO2 ceramic powder with a particle size of 28 μm, and 4 g of SiC ceramic powder with a particle size of 0.8 μm, heat to 100°C, stir for 1 hour, and obtain a polymer emulsion.
[0072] Example 11: Preparation of polymer emulsion.
[0073] Mix 2.75g of glycerol polyoxyethylene ether and 86.5g of water, add 33.3g of Fischer-Tropsch wax with a weight average molecular weight of 4000g / mol, 6.7g of polyethylene with a weight average molecular weight of 1000g / mol, 2g of AlN ceramic powder with a particle size of 63μm, 2g of ZrO2 ceramic powder with a particle size of 28μm, and 4g of SiC ceramic powder with a particle size of 0.8μm, heat to 100°C, stir for 1 hour, and obtain a polymer emulsion.
[0074] Example 12: Preparation of polymer emulsion.
[0075] Mix 2.75g of glycerol polyoxyethylene ether and 86.5g of water, add 32g of Fischer-Tropsch wax with a weight average molecular weight of 4000g / mol, 8g of polypropylene with a weight average molecular weight of 10000g / mol, 2g of AlN ceramic powder with a particle size of 63μm, 2g of ZrO2 ceramic powder with a particle size of 28μm, and 4g of SiC ceramic powder with a particle size of 0.8μm, heat to 100°C, stir for 1 hour, and obtain a polymer emulsion.
[0076] Comparative Example 1: Preparation of polymer emulsion.
[0077] This comparative example provides a polymer emulsion, which differs from Example 2 only in that the weight average molecular weight of polyethylene is different, as follows:
[0078] 4.75 g of diglycerol polypropylene glycol ether and 72.5 g of water were mixed, 60 g of polyethylene with a weight average molecular weight of 500 g / mol was added, the mixture was heated to 100° C., and stirred for 1 hour to obtain a polymer emulsion.
[0079] Comparative Example 2: Preparation of polymer emulsion.
[0080] This comparative example provides a polymer emulsion, which differs from Example 3 only in that the weight average molecular weight of polypropylene is different, as follows:
[0081] 2.75 g of glycerol polyoxyethylene ether and 94.5 g of water were mixed, 40 g of polypropylene with a weight average molecular weight of 20,000 g / mol was added, the mixture was heated to 100° C., and stirred for 1 hour to obtain a polymer emulsion.
[0082] Comparative Example 3: Preparation of polymer emulsion.
[0083] This comparative example provides a polymer emulsion, which differs from Example 9 only in that only AlN ceramic powder is used, and is as follows:
[0084] 4.75 g of diglycerol polypropylene glycol ether and 62.5 g of water were mixed, 60 g of polyethylene with a weight average molecular weight of 1000 g / mol and 10 g of AlN ceramic powder with a particle size of 63 μm were added, heated to 100° C., and stirred for 1 hour to obtain a polymer emulsion.
[0085] Comparative Example 4: Preparation of polymer emulsion.
[0086] This comparative example provides a polymer emulsion, which differs from Example 9 only in that only ZrO2 ceramic powder is used, as follows:
[0087] 4.75 g of diglycerol polypropylene glycol ether and 62.5 g of water were mixed, 60 g of polyethylene with a weight average molecular weight of 1000 g / mol and 10 g of ZrO2 ceramic powder with a particle size of 28 μm were added, heated to 100° C., and stirred for 1 hour to obtain a polymer emulsion.
[0088] Comparative Example 5: Preparation of polymer emulsion.
[0089] This comparative example provides a polymer emulsion, which differs from Example 9 only in that only SiC ceramic powder is used, as follows:
[0090] 4.75 g of diglycerol polypropylene glycol ether and 62.5 g of water were mixed, 60 g of polyethylene with a weight average molecular weight of 1000 g / mol and 10 g of SiC ceramic powder with a particle size of 0.8 μm were added, heated to 100° C., and stirred for 1 hour to obtain a polymer emulsion.
[0091] Table 1. Test results of polymer emulsion properties of Examples 1 to 7 and Comparative Examples 1 to 2.
[0092] sample Melting point(℃) Initial softening point(℃) D50(μm) Example 1 125 70 0.3 Example 2 115 90 6 Example 3 130 80 4 Example 4 122 72 0.5 Example 5 118 88 5.2 Example 6 120 74 2 Example 7 128 82 3 Comparative Example 1 105 50 1 Comparative Example 2 140 105 5
[0093] Example 13: Preparation of composite membrane.
[0094] By mass percentage, 90% of the polymer emulsion prepared in Example 1, 2% of polyurethane and 8% of carboxymethyl cellulose were uniformly rolled onto one side of a 10 μm polyethylene film. The thickness of the polymer coating was 3 μm. The film was dried to obtain a composite separator.
[0095] Example 14: Preparation of composite membrane.
[0096] By mass percentage, 80% of the polymer emulsion prepared in Example 2, 3% of polyethylene glycol and 17% of hydroxyethyl cellulose were uniformly rolled onto one side of a 10 μm polyethylene-based film. The thickness of the polymer coating was 3 μm. After drying, a composite diaphragm was obtained.
[0097] Example 15: Preparation of composite membrane.
[0098] By mass percentage, 85% of the polymer emulsion prepared in Example 3, 2.5% of polyvinyl alcohol and 12.5% of polyurethane acrylate were uniformly rolled onto one side of a 10 μm polyethylene film. The thickness of the polymer coating was 3 μm. After drying, a composite diaphragm was obtained.
[0099] Examples 16 to 24 and Comparative Examples 6 to 10: Preparation of composite diaphragms.
[0100] The polymer emulsion prepared in Example 3 in Example 15 was replaced with the polymer emulsions of Examples 4 to 12 and Comparative Examples 1 to 5, respectively, to obtain the composite diaphragms of Examples 16 to 24 and Comparative Examples 6 to 10, respectively.
[0101] Comparative Example 11: A commercial 10 μm polyethylene-based film without any coating was selected.
[0102] Comparative Example 12: A 10 μm polyethylene-based film was selected for single-sided ceramic coating, and the specific implementation process was as follows:
[0103] S1. 8 g of diglycerol polypropylene glycol ether and 62.5 g of water were mixed, 2.5 g of AlN ceramic powder having a particle size of 63 μm, 2.5 g of ZrO2 ceramic powder having a particle size of 28 μm, 5 g of SiC ceramic powder having a particle size of 0.8 μm were added, heated to 100 ° C, stirred for 1 hour, and a ceramic powder slurry was obtained;
[0104] S2. The ceramic powder slurry prepared in S1 is uniformly rolled onto one side of a 10 μm polyethylene-based film, the thickness of the ceramic coating is 3 μm, and dried to obtain a ceramic composite diaphragm.
[0105] Performance test of composite diaphragm:
[0106] Table 2. Performance test results of the composite diaphragms of Examples 13 to 24 and Comparative Examples 6 to 12.
[0107]
[0108]
[0109] It can be seen from Table 2 that the polymer emulsion of the present invention is used to prepare a composite diaphragm, which can maintain a relatively low thermal shrinkage rate and effectively reduce the thermal closure temperature.
[0110] Lithium battery capacity retention and closed-cell condition test: The composite diaphragms of Examples 13 to 24 and Comparative Examples 6 to 12 are applied to lithium batteries, wherein the positive electrode of the battery is lithium cobalt oxide and the negative electrode is graphite. The composite diaphragms of Examples 13 to 24 and Comparative Examples 6 to 12 are used to perform performance tests on assembled lithium batteries. The test results are shown in Table 3.
[0111] Table 3. Performance test results of lithium batteries prepared with the composite diaphragms of Examples 13 to 24 and Comparative Examples 6 to 12.
[0112]
[0113]
[0114] It can be seen from Table 3 that the composite diaphragms of Examples 13 to 24 and Comparative Examples 6 to 12 are closed at 120°C, and have high capacity retention rates after 900 cycles at room temperature and 85°C. The ceramic layer of Comparative Example 12 is obscured, making it difficult to determine whether it is closed.
[0115] High temperature performance test: The composite diaphragms of Examples 13 to 24, Comparative Examples 6 to 7 and Comparative Examples 11 to 12 are applied to lithium batteries, wherein the positive electrode of the battery is lithium cobalt oxide and the negative electrode is graphite. The composite diaphragms of Examples 13 to 24, Comparative Examples 6 to 7 and Comparative Examples 11 to 12 are used to perform performance tests on assembled lithium batteries. The test results are shown in Table 4.
[0116] According to GB / T 31485-2015, the battery cells assembled with the composite diaphragms of Examples 13 to 24, Comparative Examples 6 to 7 and Comparative Examples 11 to 12 were baked in a constant temperature oven at 130°C for 30 min to test whether the battery cells caught fire, exploded or leaked. The temperature was then raised to 170°C at a heating rate of 5°C / min and kept constant for 30 min to test whether the battery cells caught fire, exploded or leaked.
[0117] Table 4. High temperature performance test results of lithium batteries prepared with composite membranes.
[0118]
[0119]
[0120] It can be seen from Table 4 that the batteries assembled with the composite separators of Examples 13 to 24 have high temperature resistance.
[0121] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the above embodiments, ordinary technicians in the relevant field should understand that after reading the specification of this application, the technicians can still modify or replace the specific implementation mode of the present invention with equivalents, but these modifications or changes do not deviate from the scope of protection of the pending claims of the present application.
Claims
1. A polymer emulsion, It is characterized in that The polymer emulsion comprises the following components by weight: 20-60 parts of polymer, 4.5-10 parts of ceramic powder, 1.25-4.75 parts of emulsifier, and 62.5-116 parts of water. The polymer comprises polyolefin, and the weight average molecular weight of the polyolefin is 1000-10000 g / mol. The melting point of the polymer emulsion is 115-130° C., and the initial softening point is 70-90° C.; The ceramic powder is a combination of a first ceramic powder, a second ceramic powder and a third ceramic powder, the first ceramic powder has a particle size of 50-70 μm, the second ceramic powder has a particle size of 20-45 μm, and the third ceramic powder has a particle size of 0.5-2 μm; The weight ratio of the first ceramic powder, the second ceramic powder and the third ceramic powder is 1:1-3:0.5-2; The first ceramic powder is selected from AlN ceramic powder, and the second ceramic powder is selected from ZrO 2 Ceramic powder, the third ceramic powder is selected from SiC ceramic powder.
2. The polymer emulsion according to claim 1, It is characterized in that The D50 of the polymer emulsion is 0.3-6 μm.
3. The polymer emulsion according to claim 1, It is characterized in that The polyolefin includes at least one of polyethylene, polypropylene and Fischer-Tropsch wax.
4. The polymer emulsion according to claim 1, It is characterized in that The polyolefin is selected from a combination of Fischer-Tropsch wax and polyethylene; The polyolefin is selected from a combination of Fischer-Tropsch wax and polypropylene.
5. A polymer composite diaphragm, It is characterized in that It comprises a base film and a polyolefin coating composited on at least one side of the base film, wherein the material of the polyolefin coating comprises the polymer emulsion described in any one of claims 1 to 4.
6. The polymer composite membrane according to claim 5, It is characterized in that The thickness of the polyolefin coating is 1-6 μm.
7. Use of the polymer composite diaphragm according to any one of claims 5 to 6 in a lithium battery diaphragm.
Citation Information
Patent Citations
Separation membrane and preparation method thereof, and lithium ion battery using the separation membrane
CN105098121A
Low-molecular-weight polyolefin emulsion applied to seed coating agent film-forming agent and preparation method of low-molecular-weight polyolefin emulsion
CN111019220A
Organic coating / polyethylene composite diaphragm and preparation method thereof and lithium ion battery
CN111192996A
Functional coating diaphragm for lithium ion battery, and preparation method thereof
CN111509173A
Polypropylene composite diaphragm with low-temperature thermal hole closing mechanism, preparation method of polypropylene composite diaphragm and lithium ion battery
CN113078414A
